Educação inclusiva: um enfoque histórico no município de Cascavel - PR dos anos de 1952 a 2023 - Granetto, Luiz Fernando (2024)
This master's thesis investigated the trajectory of inclusive education in Cascavel - PR, connecting it to national and local historical contexts. From this perspective, based on the historical-dialectical materialist method and through bibliographic research, it was analyzed how political, economic, and social factors shaped the educational development in the region, with emphasis on the inclusion of people with disabilities. It is noteworthy that the research is characterized as applied and qualitative, with an exploratory character, as it aims at greater familiarity with the theme, pondering the importance of debates and references about this proposition. The research begins by conceptually situating itself and exploring national landmarks and then outlines the local panorama from the decay of the obrage system to the planned colonization. The methodology involved analysis of data, indicators, and historical sources, providing a multifaceted understanding. The bibliographic survey was carried out at different times, and initially, the Capes and SciELO platforms were used based on the descriptors: History of education, person with disabilities, inclusion, inclusive education, and Cascavel - PR. In addition to the references found, reference works within the areas of History of Education and Inclusive Education were added to the initial survey, as well as legislation and documents cited in the works found in the searches, which demonstrated relevance for the analysis and the research cut. Population growth driven by agribusiness in the 1960s and 1970s was evidenced, mobilizing the need for more educational institutions. The creation of entities and associations reflects the mobilization of the community in favor of inclusion, highlighting the importance of the active participation of teachers and parents. Municipal legislation and affirmative actions in higher education, such as quotas for people with disabilities, represent recent advances in Cascavel - PR. The results point to the relevance of the research in understanding the historical development of inclusive education in the municipality. Among the final considerations, the inclusion of people with disabilities is presented not only as a challenge overcome but as a continuous and integral commitment of the community, indicating their significant contribution to the understanding of inclusive education in regional contexts.